GM-CSF-activated STAT5A regulates macrophage functions and inflammation in atherosclerosis - Nagenborg, Jan; Jin, Han; Ruder, Adele V.; Temmerman, Lieve; Mees, Barend; Schalkwijk, Casper; Müller-Klieser, Daniel; Berg, Thorsten; Goossens, Pieter; Donners, Marjo M. P. C.; Biessen, Erik A. L. (Frontiers in Immunology, 2023)
Inhibition of STAT5 was recently reported to reduce murine atherosclerosis. However, the role of STAT5 isoforms, and more in particular STAT5A in macrophages in the context of human atherosclerosis remains unknown. Here, we demonstrate reciprocal expression regulation of STAT5A and STAT5B in human atherosclerotic lesions. The former was highly upregulated in ruptured over stable plaque and correlated with macrophage presence, a finding that was corroborated by the high chromosomal accessibility of STAT5A but not B gene in plaque macrophages. Phosphorylated STAT5 correlated with macrophages confirming its activation status. As macrophage STAT5 is activated by GM-CSF, we studied the effects of its silencing in GM-CSF differentiated human macrophages. STAT5A knockdown blunted the immune response, phagocytosis, cholesterol metabolism, and augmented apoptosis terms on transcriptional levels. These changes could partially be confirmed at functional level, with significant increases in apoptosis and decreases in lipid uptake and IL-6, IL-8, and TNFα cytokine secretion after STAT5A knockdown. Finally, inhibition of general and isoform A specific STAT5 significantly reduced the secretion of TNFα, IL-8 and IL-10 in ex vivo tissue slices of advanced human atherosclerotic plaques. In summary, we identify STAT5A as an important determinant of macrophage functions and inflammation in the context of atherosclerosis and show its promise as therapeutic target in human atherosclerotic plaque inflammation.